A new approach to urinalysis: effectiveness of a contingency management program among adolescent offenders in Spain - Fernández-Moreno, Álvaro; Roncero, David; Moreno-Fernández, Román D. (Frontiers in Psychology, 2024)
Background When addressing antisocial behaviour among adolescents, programs based on the paradigm of positive psychology through enhancing self-efficacy have demonstrated their effectiveness in furthering the positive development of young people with a history of antisocial behaviour. Nevertheless, there has been little research into the effectiveness of these type of programs in mitigating substance abuse among juvenile offenders. The aim of this paper is to analyse the effectiveness of a contingency management program in reducing the prevalence of relapses into drug consumption among adolescents who have committed serious crimes. Methods The study consisted of a sample of 91 male adolescents, between 15 and 19 years, in juvenile detention, who were divided into two treatment groups. For both groups, biological testing was used to detect drug consumption upon their re-turn from leave permits from the Centre. Results The quasi-experimental group had significantly lower rates of relapse than the quasi-control group. Furthermore, being part of the quasi-experimental group was a significant predictor of reduced rates of relapses. Conclusion The results suggest that the incorporation of treatment strategies which reinforce feelings of self-efficacy and adequate orientation towards the future, as a complement to disciplinary sanctions, are effective in reducing relapses in drug use among adolescent offenders.